Theatre Reviews - Bogdańska, Olga; D’Auria, Verónica; Heijes, Coen; Georgopoulou, Xenia (Multicultural Shakespeare: Translation, Appropriation and Performance, 2013)
The Tempest. Dir. Silviu Purcarete. The National Theatre “Marin Sorescu” of Craiova, Romania. 16th Shakespeare Festival, Gdansk, Poland Richard III. Dir. Gabriel Villela. Blanes Museum Garden, Montevideo, Uruguay Henry V. Dir. Des McAnuff. Stratford Shakespeare Festival, Ontario, Canada Julius Caesar. Dir. Gregory Doran. Royal Shakespeare Company A Midsummer Night’s Dream. Adapted and dir. Georgina Kakoudaki. Theatre groups _2 and 4Frontal, Theatro tou Neou Kosmou, Greece Julius Caesar: Scripta Femina. Dir. Roubini Moschochoriti. Theatre group Anima Kinitiras Studio, Greece